2015
DOI: 10.1007/s10295-015-1586-9
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization ofPseudomonas fluorescenslipase on hydrophobic supports and application in biodiesel synthesis by transesterification of vegetable oils in solvent-free systems

Abstract: This work describes the preparation of biocatalysts for ethanolysis of soybean and babassu oils in solvent-free systems. Polystyrene, Amberlite (XAD-7HP), and octyl-silica were tested as supports for the immobilization of Pseudomonas fluorescens lipase (PFL). The use of octyl-silica resulted in a biocatalyst with high values of hydrolytic activity (650.0 ± 15.5 IU/g), immobilization yield (91.3 ± 0.3 %), and recovered activity (82.1 ± 1.5 %). PFL immobilized on octyl-silica was around 12-fold more stable than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 63 publications
1
46
1
Order By: Relevance
“…Talukder et al [11] reported that in the methanolysis of free fatty acids catalyzed by Novozym 435 (CALB immobilized on acrylic resin), the highest initial reaction rate was achieved at 60 °C, but that the maximum biodiesel yield at this temperature was slightly lower than at 40 °C. A 1:7 HWCO/ethanol molar ratio was chosen on the basis of the work by Lima et al [30], who studied the enzymatic transesterification of vegetable oils using ethanol as acyl acceptor. Although the stoichiometric molar ratio for the esterification of FFAs is 1:1, excess ethanol was used to displace the esterification equilibrium towards the products.…”
Section: Esterification Of Hwco With Ethanolmentioning
confidence: 99%
“…Talukder et al [11] reported that in the methanolysis of free fatty acids catalyzed by Novozym 435 (CALB immobilized on acrylic resin), the highest initial reaction rate was achieved at 60 °C, but that the maximum biodiesel yield at this temperature was slightly lower than at 40 °C. A 1:7 HWCO/ethanol molar ratio was chosen on the basis of the work by Lima et al [30], who studied the enzymatic transesterification of vegetable oils using ethanol as acyl acceptor. Although the stoichiometric molar ratio for the esterification of FFAs is 1:1, excess ethanol was used to displace the esterification equilibrium towards the products.…”
Section: Esterification Of Hwco With Ethanolmentioning
confidence: 99%
“…Numerous microorganisms are known to produce lipases when incubated with lipid substrates (Haba et al 2000). The majority of bacterial lipases originate from Gram-negative bacteria, the most valuable being Pseudomonas, which includes at least 7 lipaseproducing species, which are P. aeruginosa (Prasad 2014;Tielen et al 2013), Pseudomonas cepacia (Badgujar et al 2016;Cao et al 2016;Sasso et al 2016), Pseudomonas alcaligenes (Chen et al 2014;Patel et al 2014), Pseudomonas glumae (Knapp et al 2016), P. fluorescens (Guldhe et al 2015;Lima et al 2015;Xun et al 2012), Pseudomonas fragi (Dey et al 2014;Santarossa et al 2005), and Pseudomonas putida (Fatima et al 2014). …”
Section: Microorganisms Producing Lipasesmentioning
confidence: 99%
“…Activities of the biocatalysts CALB-SMMP-octyl and CALB-SMMPoctyl-glu were similar, although recovered activities were different for those biocatalysts. This difference indicates mass transfer delays into the internal surface of the biocatalyst, very common for highloaded biocatalysts [1,2,4,21].…”
Section: Characterization Of the Smmpsmentioning
confidence: 99%
“…Most of the enzymes, including lipases for synthesis in organic medium, have their stability and reusability improved by immobilization onto solid supports [1][2][3]. Although several immobilized lipases are commercially available (e.g., Novozym 435, Amano lipase PS, etc.…”
Section: Introductionmentioning
confidence: 99%